MORPHOLOGICAL STUDIES OF SOME MARINE MASTOGLOIA (BACILLARIOPHYCEAE) BELONGING TO SECTION SULCATAE, INCLUDING THE DESCRIPTION OF NEW SPECIES - Pennesi, Chiara (Journal of phycology, 2012)
© 2012 Phycological Society of America.